Carbon dioxide and water co-adsorption on the low-index surfaces of TiC, VC, ZrC and NbC: a DFT study. Issue 20 (14th May 2019) - Quesne, Matthew G.; Roldan, Alberto; de Leeuw, Nora H.; Catlow, C. Richard A.
Abstract : We present a theoretical DFT study into the activation of CO2 and H2 O by four low-index surfaces of TiC, VC, ZrC and NbC. Two distinct chemisorption pathways are found for CO2 activation, whilst multiple surface mediated interactions between H2 O and CO2 are reported. Abstract : We present a theoretical DFT study into the activation of CO2 by TiC, VC, ZrC and NbC. Particular focus is given to the study of CO2 /H2 O co-adsorption and interaction on four carbide low-index surfaces: 001, 011, carbon-terminated 111 and metal-terminated 111. The adsorption and activation of CO2 is shown to be most exothermic and indeed barrierless on the metal-terminated 111 surfaces, whilst adsorption on the 001 and 011 planes occurs via a small activation energy barrier. In contrast, the carbon-terminated 111 surface proves to be unstable in the presence of the adsorbates. Both water and carbon dioxide adsorb most strongly on TiC and most weakly on NbC, with the strongest co-adsorption interactions being seen in conformations that maximise hydrogen-bonding.